COMPETITIVE EFFECTS OF THE ALIEN INVASIVE CENTAUREA SOLSTITIALISL. ON TWO CHILEAN BACCHARIS SPECIES AT DIFFERENT LIFE-CYCLE STAGES EFECTOS COMPETITIVOS DE LA ALOCTONA INVASORA CENTAUREA SOLSTITIALIS L. SOBRE DOS ESPECIES CHILENAS DE BACCHARIS EN DIFERENTES ESTADOS DEL CICLO DE VIDA - Susana Gómez-González (Universidad de Concepción, 2009)
Several studies have revealed a variety of mechanisms of invasion of alien plant species. However, little is known on how those mechanisms and their associated effects on native species change across different life-cycle stages. Under controlled conditions, we assessed the interactions between the alien invasive species Centaurea solstitialis L. (Asteraceae) and two pioneer native species to the Chilean matorral; Baccharis linearis (Ruiz et Pav.) Pers. and B. paniculata DC. (Asteraceae). Competitive effects of the invader on natives were evaluated by combining different life-cycle stages: seed-seed, plant-seed, and plant-plant. Seed germination of C. solstitialis was explosive and much faster than that of the native species. The presence of C. solstitialis (individuals or seeds) did not affect negatively the seed germination of the two Baccharis species. However, the presence of C. solstitialis plants significantly decreased the total biomass oí Baccharis plants. Thus, the effect of C. solstitialis on Baccharis species depended on the life-cycle stage at which the interactions occurred. In the Chilean matorral, the early emergence of C. solstitialis could be an important invasion mechanism, enabling established plants to competitively displace late emerging seedlings of Baccharis species. The huge abundance of C. solstitialis in some disturbed matorrals suggests that seedling establishment of these two pioneer species could be limited. Varios estudios han revelado una variedad de mecanismos de invasión en las plantas alóctonas. Sin embargo, aún se conoce poco sobre cómo tales mecanismos y sus efectos asociados cambian a través de diferentes estados del ciclo vida. En este estudio evaluamos, bajo condiciones controladas, el resultado de las interacciones competitivas entre la especie invasora Centaurea solstitialis L. (Asteraceae) y dos especies pioneras nativas del matorral chileno; Baccharis linearis (Ruiz et Pav.) Pers. y B. paniculata DC (Asteraceae). Estas interacciones fueron evaluadas combinando diferentes estados del ciclo de vida: semilla-semilla, planta-semilla y planta-planta. La germinación de C. solstitialis fue explosiva, siendo mucho más rápida que la de las especies nativas. La presencia de C. solstitialis (plantas o semillas) no disminuyó la germinación de las especies nativas de Baccharis. Sin embargo, la presencia de plantas establecidas de C. solstitialis disminuyó significativamente la biomasa de las plantas de Baccharis. Entonces, el efecto de C. solstitialis sobre las especies de Baccharis varió en función del estado del ciclo de vida en el cual las interacciones ocurrieron. En el matorral chileno, la emergencia temprana y explosiva de C. solstitialis podría ser un importante mecanismo de invasión, ya que aquellas plantas prontamente establecidas podrían desplazar competitivamente a las plántulas de Baccharis que emergen más tarde. La enorme abundancia de C. solstitialis en algunas zonas de matorral sugiere que el establecimiento de plántulas de estas dos especies pioneras podría estar siendo limitado.